2018
DOI: 10.1140/epjds/s13688-018-0135-y
|View full text |Cite
|
Sign up to set email alerts
|

Success in books: a big data approach to bestsellers

Abstract: Reading remains the preferred leisure activity for most individuals, continuing to offer a unique path to knowledge and learning. As such, books remain an important cultural product, consumed widely. Yet, while over 3 million books are published each year, very few are read widely and less than 500 make it to the New York Times bestseller lists. And once there, only a handful of authors can command the lists for more than a few weeks. Here we bring a big data approach to book success by investigating the prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
43
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 25 publications
3
43
1
1
Order By: Relevance
“…Research in developmental psychology has studied careers of prominent artists and scientists for decades, advocating the importance of chance for the successful unfolding of careers in various creative domains [1,2,3,4]. In recent years, the availability of big databases on scientific publications [5] and artistic records, from books to movies [6,7,8], has made it possible to test a number of previously suggested hypotheses on a large scale. For instance, in previous work [9,10] the analysis of thousands of creative careers has shown that the biggest hit of an individual occurs randomly within an individual's career, a finding named the equal-odds-rule [3].…”
Section: Introductionmentioning
confidence: 99%
“…Research in developmental psychology has studied careers of prominent artists and scientists for decades, advocating the importance of chance for the successful unfolding of careers in various creative domains [1,2,3,4]. In recent years, the availability of big databases on scientific publications [5] and artistic records, from books to movies [6,7,8], has made it possible to test a number of previously suggested hypotheses on a large scale. For instance, in previous work [9,10] the analysis of thousands of creative careers has shown that the biggest hit of an individual occurs randomly within an individual's career, a finding named the equal-odds-rule [3].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work [16], we analyzed and modeled the dynamics of book sales, identifying a series of reproducible patterns: (i) most bestsellers reach their sales peak in less than ten weeks after release; (ii) sales follow a universal "early peak, slow decay" pattern that can be described by an accurate statistical model; (iii) we showed that the formula predicted by the model helps us predict future sales. Yet, to accurately predict the future sales using the model of Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, to accurately predict the future sales using the model of Ref. [16], we need at least the first 25 weeks of sales after publication, a period within which most books have already reached their peak sales and started to lose momentum. Therefore, predictions derived from this statistical model, potentially useful for long-term inventory management, are not particularly effective for foreseeing the sales potential of a new book.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies [37,56] emphasized the individuals' limited attention as a determinant for the viral popularity of low-quality items. Other recent works focused on modelling the interplay between quality/talent and popularity for diverse types of agents, including websites [20], scientific papers [30,55], researchers [29,50], and bestseller books [58]. Both model-based [20,30] and experimental results [43] indicate that in presence of social influence, the relation between popularity and quality is highly non-linear, meaning that a small variation of quality leads to large variations in popularity.…”
Section: Introductionmentioning
confidence: 99%